2014
DOI: 10.1073/pnas.1419632111
|View full text |Cite
|
Sign up to set email alerts
|

GABAρ subunits confer a bicuculline-insensitive component to GFAP + cells of cerebellum

Abstract: GABA-A receptors mediating synaptic or extrasynaptic transmission are molecularly and functionally distinct, and glial cells are known to express a plethora of GABA-A subunits. Here we demonstrate that GFAP + cells of the granular layer of cerebellum express GABAρ subunits during early postnatal development, thereby conferring peculiar pharmacologic characteristics to GABA responses. Electron microscopy revealed the presence of GABAρ in the plasma membrane of GFAP + cells. In contrast, expression in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The lack of muscimol response in astrocytes was surprising considering that functional expression of GABAARs was demonstrated in Bergmann glia at P5-P7 and GABAAmediated signaling at P20-P30 was drastically reduced or undetectable (Müller et al, 1994), suggesting that while GABAA signaling is important through early postnatal development of the cerebellum, there is an apparently different regulation for WM. In support of this hypothesis, functional expression of GABAARs was also reported in ependymal glial cells from the cerebellum located at the roof of the fourth ventricle (Reyes-Haro et al, 2013a), while immunofluorescence studies revealed the expression of the GABAAρ1 subunit in astrocytes from the granular layer of the cerebellar lobule X (Pétriz, et al, 2014). Astrocytes from WM give rise to interneurons of the molecular layer during the postnatal development of the cerebellum (Silbereis et al, 2009).…”
Section: Gabaa Is Functionally Expressed In Ng2 Gliamentioning
confidence: 66%
See 1 more Smart Citation
“…The lack of muscimol response in astrocytes was surprising considering that functional expression of GABAARs was demonstrated in Bergmann glia at P5-P7 and GABAAmediated signaling at P20-P30 was drastically reduced or undetectable (Müller et al, 1994), suggesting that while GABAA signaling is important through early postnatal development of the cerebellum, there is an apparently different regulation for WM. In support of this hypothesis, functional expression of GABAARs was also reported in ependymal glial cells from the cerebellum located at the roof of the fourth ventricle (Reyes-Haro et al, 2013a), while immunofluorescence studies revealed the expression of the GABAAρ1 subunit in astrocytes from the granular layer of the cerebellar lobule X (Pétriz, et al, 2014). Astrocytes from WM give rise to interneurons of the molecular layer during the postnatal development of the cerebellum (Silbereis et al, 2009).…”
Section: Gabaa Is Functionally Expressed In Ng2 Gliamentioning
confidence: 66%
“…Classically, the astrocyte-like precursor cells are responsive to GABA in multiple brain regions, such as the hippocampus (Seri et al, 2001, Ge et al, 2006 and sub-ventricular zones (Bolteus andBordey, 2004, Liu et al, 2005). Functional expression of GABAARs has been demonstrated in diverse glial cells from the cerebellum, for example in Bergmann's glia (Müller et at., 1994), in ependymal cells from the periventricular zone (Reyes-Haro et al, 2013) and in primary cultures of cerebellar astrocytes (Pétriz et al, 2014). Moreover, the functional expression of GABAARs in NG2 glial cells from cerebellar WM was also reported (Zonouzi et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Parental support interacted with two GABA‐related genes (gamma‐aminobutyric acid): GABRR1 and GABRR2 (both genes coding for subunits of the GABA A ‐rho receptor, formerly known as GABA C ‐receptor (Enz, ; D. Zhang, Pan, Awobuluyi, & Lipton, )). It is well‐known that both GABA A and GABA A ‐rho receptors are ionotropic receptors, but the exact mechanism of different subunits involved in the GABA A ‐rho receptor function in the central nervous system remains unclear (Olsen & Sieghart, ; Pétriz, Reyes‐Haro, González‐González, Miledi, & Martínez‐Torres, ; Yoon & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, GABA‐ρ receptors express as homomeric ion channels, and some studies suggest pseudoheteromeric channels consisting of different ρ subunits (Connolly et al, ). There is some limited in vitro evidence to support co‐assembly of ρ subunits with other GABA A subunits, particularly with α1 and γ2 (Milligan et al, ; Pétriz et al, ), and also with glycine receptor α1 and α2 subunits (Pan et al, ).…”
Section: Ionotropic Gaba Receptor Subunit Compositionmentioning
confidence: 99%
“…The presence of GABA ρ1 and ρ2 subunits, either homomerically or combined with other GABA A (α1 and γ2) subunits, has also been identified in cultured cerebellar astrocytes. It is proposed that these GABA‐ρ subunits may contribute to the regulation of glial development in the cerebellum (Pétriz et al, ). Although GABA‐ρ receptors are mainly expressed in the CNS, they are also found in the peripheral nervous system, for example, in the gastrointestinal tract (Jansen et al, ), and sperm cells (Li et al, ).…”
Section: Gaba‐ρ Receptorsmentioning
confidence: 99%